Análisis de la sustitución de fuentes energéticas en Bolivia - Javier Aliaga Lordemann; Alejandro Capriles (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2011)
– The present document analyzes the energy substitution elasticities in the short and long term in Bolivia. The inputs accounted are electricity, hydrocarbons and biomass. In order to measure and identify the direction of the elasticities we use a Transcendental Logarithmic Production Function, known as Translog, defined as block model. We also derive the short term model, known as pair model.
Keywords: D29; C51; Q49; 330; Energiesubstitution; Bolivien